THE ANALYSIS OF SECONDARY SCHOOL STUDENTS' TRANSITION SITUATIONS IN MULTIPLE REPRESENTATIONS - Mehmet Altan Kurnaz; Nezihe Gökçen Bayri (International Council of Associations for Science Education, 2018)
In this article, the relationships between students’ personal relationship to the concept of pressure and teaching conditions of this concept were investigated in terms of the Anthropological Theory of Didactics. To determine these complex relationships, first an institutional analysis was conducted, and in this same manner, the textbook has been analyzed to uncover the institutional eelationship to the concept of pressure, and second, an achievement test has been used to gather data to uncover personal relationship to concept of pressure. 348 8th-grade students who successfully completed the pressure topic in their science classes participated in this study. The gathered data were analyzed in a descriptive and qualitative way. The results of this study emphasize the relationship between the teaching conditions and the students’ understanding of pressure and support the need for multiple representations to teach effectively the pressure concept.
Keywords: pressure; Science; secondary education; Q; Theory and practice of education; transitions in representations; LB5-3640; anthropological theory of didactics; 4. Education